Meningkatkan Pemahaman Siswa tentang Teorema Pythagoras dengan Kotak Musik Spiral Theodorus - Maslina Simanjuntak (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2018)
The background of this journal is because of the low understanding level of students regarding the Pythagoras theorem. It is visile from the inability of students in deciding the Hypotenuse on right triangle and students often see the Pythagoras theorem formulas as a same. Even though both formulas may not be the same, they must firstly be defined what does it mean a,b,c. Writer is interested in solving those problems by using Spiral Theodorus music box as instructional media. The basic concept that writer use during the making of this media is to connect the Pythagoras concept with Spiral Theodorus. It is because writer think Spiral Theodorus use Pythagoras concept. This musix box can be used everyday by students so that the more often student used and see the Spiral Theodorus music box, the more they will increase their understanding about Pythagoras theorem. Keywords: Pythagoras, Kotak Musik Spiral Theodorus.